XR and mental wellbeing: state of the art and future research directions for the Metaverse - Taylor, Alexandra; tom Dieck, M. Claudia; Jung, Timothy; Cho, Justin; Kwon, Ohbyung (Frontiers in Psychology, 2024)
Introduction The purpose of this study is to provide an overview of extant research regarding XR technology and its effect on consumer wellbeing. With the hopes of informing marketing practitioners on XR consumer psychology, in preparation for the Metaverse. Methods To achieve the above aim, two types of analysis took place. Firstly, a bibliometric analysis was conducted which was then followed by a framework-based structured literature review. The latter entailed an analysis of 81 articles evaluated from a positive psychological approach. Findings Following the TCCM framework, the analysis revealed the most common psychological theories demonstrating potential avenues for XR to impact consumer wellbeing. Moreover, researchers found preliminary links between, theory, characteristics, and contexts. Giving a preliminary description of how theory manifests into reality. Finally, the overview of extant literature was used to propose new avenues for future research pertaining to marketing, the Metaverse, and consumer effects. Conclusion In conclusion, the paper provides stakeholder insights which can ensure minimal consumer risk and sustainable use of the XR technology and Metaverse. While addressing the need for more research that uncovers the psychological effects of emerging technologies, so to prepare for the Metaverse. This is especially important when considering the current upsurge of these technologies and the uncertainties associated with their novelty and the idea of an ‘always on’ consumer.